Photocatalysts: Steering Hollow Multishelled Structures in Photocatalysis: Optimizing Surface and Mass Transport (Adv. Mater. 44/2020). Issue 44 (3rd November 2020) - Wei, Yanze; Yang, Nailiang; Huang, KeKe; Wan, Jiawei; You, Feifei; Yu, Ranbo; Feng, Shouhua; Wang, Dan
Abstract : In article number 2002556, Shouhua Feng, Dan Wang, and co‐workers give an overview of rational design to elevate the photocatalytic performance of hollow multishelled structures (HoMSs) by surface and mass‐transfer optimization. Enlarged effective surface areas and the boosted mass transport in HoMSs greatly favor the energy/mass transfer processes in photocatalysis. In addition, specific structural and compositional parameters affecting photocatalytic performance are described, along with proposed guidance for the development directions of HoMS photocatalysts.